Comparative Stress Analysis of Balanced Cantilever Bridges Using MIDAS Civil Based on AASHTO, Eurocode, and IRC - Priesta Stephan Hutagalung; Tavio (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Evaluating stress behavior in prestressed concrete girders during staged construction is important for structural safety. This study compares stress responses based on three design codes: AASHTO, Eurocode, and IRC. A total of 21 construction stages were simulated using MIDAS Civil 2023 to model a balanced cantilever bridge. The analysis included time-dependent effects such as creep, shrinkage, and prestress losses, following each code’s assumptions. To ensure fair comparison, material properties, geometry, and environmental conditions were kept uniform. Results show that the highest compressive stress at the top fiber occurred in the Eurocode model (11,960 kPa), while the highest tensile stress was found in the IRC model (841.3 kPa). At the bottom fiber, IRC also produced the highest compressive (18,630 kPa) and tensile stresses (1,282 kPa). These differences indicate variations in how each code accounts for viscoelastic behavior and stress redistribution. This study highlights the importance of developing a national design standard in Indonesia that balances safety and efficiency by adapting insights from international codes.